An iterative algorithm to approximate a common element of the set of common fixed points for a finite family of strict pseudo-contractions and of the set of solutions for a modified system of variational inequalities - Atid Kangtunyakarn (My University, 2013)
In this paper, we introduce a new iterative algorithm for finding a common element of the set of fixed points of a finite family of -strictly pseudo-contractive mappings and the set of solutions of new variational inequalities problems in Hilbert space. By using our main results, we obtain an interesting theorem involving a finite family of κ-strictly pseudo-contractive mappings and two sets of solutions of the variational inequalities problem.
Keywords: Finite set; Optimization and Variational Analysis